Magnetic moment evolution and spin freezing in doped BaFe2As2 - Jonathan Pelliciari (Nature Portfolio, 2017)
Abstract Fe-K β X-ray emission spectroscopy measurements reveal an asymmetric doping dependence of the magnetic moments μ bare in electron- and hole-doped BaFe2As2. At low temperature, μ bare is nearly constant in hole-doped samples, whereas it decreases upon electron doping. Increasing temperature substantially enhances μ bare in the hole-doped region, which is naturally explained by the theoretically predicted crossover into a spin-frozen state. Our measurements demonstrate the importance of Hund’s-coupling and electronic correlations, especially for hole-doped BaFe2As2, and the inadequacy of a fully localized or fully itinerant description of the 122 family of Fe pnictides.